Mindfulness-based intervention in Chinese pregnant women with recurrent miscarriage: A non-randomized controlled study. (December 2021) - Wang, Dan-Ni; Weng, Xue-Ling; Gao, Ling-Ling
Abstract: Objective: Pregnant women with recurrent miscarriage have high rates of anxiety and depression. Mindfulness-based interventions have shown benefits in improving mental health in diverse populations; however, few studies have explored their efficacy in pregnant women with recurrent miscarriage, which was investigated in the present study. Design: A nonrandomized controlled study was carried out from August 2019 to November 2020. Setting: The study was conducted at a regional teaching hospital in Guangzhou, China that provides leading care for recurrent miscarriage. Participants: A total of 158 pregnant women with recurrent miscarriage were recruited and allocated to the intervention group ( n  = 79) or the control group ( n  = 79); 131 women completed the study. Intervention: The mindfulness-based intervention consisted of a 1-h education session and daily mindfulness exercises guided by audio recordings during hospitalization. Measurements and findings: Study outcomes included perceived stress measured with the Perceived Stress Scale; symptoms of anxiety and depression measured with the Self-rating Anxiety Scale and Edinburgh Postnatal Depression Scale, respectively; and positive and negative affect measured with the Positive Affect and Negative Affect Scale – Revised, respectively. Compared to the control group, participants in the intervention group showed significant decreases in perceived stress, depression symptoms, and negative affect and an increase in positive affect after the intervention. Anxiety increased significantly in the control group during the study but remained unchanged in the intervention group. Key conclusions: A mindfulness-based intervention can reduce psychological symptoms and improve mental health in pregnant women with recurrent miscarriage. Implications for practice: A mindfulness-based intervention should be incorporated into routine care to help improve the mental health of pregnant women with recurrent miscarriage.